1998
DOI: 10.1136/adc.78.6.518
|View full text |Cite
|
Sign up to set email alerts
|

Development and progression of microalbuminuria in a clinic sample of patients with insulin dependent diabetes mellitus

Abstract: The evolution of abnormal albumin excretion and its association with suggested risk factors were studied in 233 children with insulin dependent diabetes mellitus (IDDM) attending a single paediatric diabetic clinic over an eight year period. Yearly albumin:creatinine ratios (ACR; measured in mg/mmol) in early morning urine samples, glycated haemoglobin (HbA1c), and blood pressure were recorded. Thirty four (14.5%) children had a persistently raised ACR (ACR > 2.5 mg/ mmol on at least three consecutive occasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 39 publications
6
21
3
Order By: Relevance
“…RESEARCH DESIGN AND METHODS -Between 1986 and 1995, 511 subjects aged Ͻ16 years were recruited at diagnosis and followed for a median of 6 years (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. In 78 subjects (designated cases), an annual assessment of the albumin-to-creatinine ratio (ACR) in three morning first-void urine samples detected MA (males: ACR Ն3.5 mg/mmol, females: ACR Ն4.0 mg/mmol in two of three urine samples).…”
Section: Risk Of Nephropathy Can Be Detected Before the Onset Of Micrmentioning
confidence: 99%
See 1 more Smart Citation
“…RESEARCH DESIGN AND METHODS -Between 1986 and 1995, 511 subjects aged Ͻ16 years were recruited at diagnosis and followed for a median of 6 years (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. In 78 subjects (designated cases), an annual assessment of the albumin-to-creatinine ratio (ACR) in three morning first-void urine samples detected MA (males: ACR Ն3.5 mg/mmol, females: ACR Ն4.0 mg/mmol in two of three urine samples).…”
Section: Risk Of Nephropathy Can Be Detected Before the Onset Of Micrmentioning
confidence: 99%
“…Nevertheless, only a proportion (30-50%) of subjects with type 1 diabetes is at risk for nephropathy (1), and genetic factors are thought to be important in determining susceptibility (2). During adolescence, HbA 1c , sex, and puberty (3,4) are also important determinants of the risk for incipient nephropathy (microalbuminuria [MA]). However, it may be possible to detect individuals at risk at an earlier stage in the pathogenesis of nephropathy.…”
mentioning
confidence: 99%
“…Most studies investigating microalbuminuria have been cross-sectional and clinic based, with only a few being longitudinal, but mainly with a retrospective design. Jones et al (Jones et al, 1998) reported a prevalence of 14.5% during 8.5 years of diabetes duration, whereas Rudberg et al (Rudberg et al, 1993) reported a prevalence of 24% after 15 years diabetes duration. The most recent data from the Oxford Regional Prospective Study (ORPS), a population-based inception cohort of children with type 1 diabetes, has shown a cumulative prevalence of microalbuminuria of 25.7% after 10 years and of 50.7% after 19 years of diabetes duration (Amin et al, 2008).…”
Section: Early Manifestations Of Diabetic Nephropathy In Youth With Tmentioning
confidence: 99%
“…Microalbuminuria often develops during puberty, whereas its prevalence during prepubertal years is rare (Janner et al, 1994;Lawson et al, 1996;Norgaard et al, 1989;Rudberg et al, 1993). The overall prevalence of microalbuminuria in youth with type 1 diabetes ranges between 4 and 26% (Bojestig et al, 1996;Cook and Daneman, 1990;Dahlquist and Rudberg, 1987;Joner et al, 1992;Jones et al, 1998;Mathiesen et al, 1986;Moore and Shield, 2000;Norgaard et al, 1989;Olsen et al, 2000;Rudberg et al, 1993;Schultz et al, 1999b). This large variation in the prevalence of microalbuminuria is due to differences in study design, duration of diabetes, age range, and glycemic control.…”
Section: Early Manifestations Of Diabetic Nephropathy In Youth With Tmentioning
confidence: 99%
See 1 more Smart Citation